Pola Komunikasi Remaja dengan Ibu, Pola Komunikasi Ibu dengan Guru, dan Pencapaian Akademik Remaja - Herien Puspitawati; Anisyah Kusumawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
This study aimed to analyze the influence of family characteristics, adolescent-mother communication pattern, adolescent-mother communication pattern and teacher-mother communication pattern to academic achievement. The specified sample has the criteria of adolescents still having mothers and live with mothers totaling 71 adolescents consisting of 31 boys and 40 girls, chosen purposively by research sites in high school in Bogor City. Data is collected by self-administrated. The results showed a significant difference in the communication of the orientation dimension of adolescent conversation with mothers in teenage boys and girls, with common answers of teenage girls higher than a male adolescent. Communication of adolescents with mothers is still based on the orientation dimension of the conversation and the orientation of conformity categorized quite well. While mother communication with teacher showed the result which still classified as still good enough, but still found also almost one fourth communications mother with the teacher (23,9%) which is low. Based on the regression test showed that factors that have a significant positive effect on academic achievement are maternal age and adolescent communication with mothers according to teenage answers.